2022
DOI: 10.3389/fsurg.2022.940856
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Urgent liver pathologies: All in one

Abstract: Ruptured hepatocellular carcinoma (HCC) is a well-known serious complication of this most common primary liver malignancy. However, when HCC rupture is associated with other focal liver lesions, the diagnosis and therapy may be very challenging. Correct differentiation of focal liver lesions is of paramount importance for successful treatment. The aim of this report is to present a unique case of HCC rupture complicated with liver abscess, hematoma and portal vein thrombosis. We discuss possible pathophysiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Additionally, HAIC may be beneficial since it decreases tumor size and by this, it reduces the risk of HCC rupture. 15 For patients with particular large tumors (>7 cm), the OS after TACE was only 11.2–13.2 months. 16 , 17 Therefore, patients with huge mass HCC and PVTT were included in the study and are reported in this report.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HAIC may be beneficial since it decreases tumor size and by this, it reduces the risk of HCC rupture. 15 For patients with particular large tumors (>7 cm), the OS after TACE was only 11.2–13.2 months. 16 , 17 Therefore, patients with huge mass HCC and PVTT were included in the study and are reported in this report.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) accounts for 75%-85% of primary liver cancers (PLC) which is a common cancer worldwide with bad prognosis and maybe associated serious complications such as tumor rupture, and so on. It is the fourth leading cause of cancer-related deaths worldwide, and generally occurs in the context of chronic liver disease at the cirrhosis stage ( 1 , 2 ). Patients with HCC are usually diagnosed in advanced stages, with very limited therapeutic options and bleak outcomes.…”
Section: Introductionmentioning
confidence: 99%